Dialysis and driving: an anonymous survey of patients receiving dialysis for end‐stage kidney disease. Issue 10 (18th October 2021) - Graver, Alison; Odell, Morris; Churilov, Leonid; Power, David A.; Mount, Peter F.; Davies, Matthew R. P.; Choy, Suet‐Wan; Paizis, Kathy; Cook, Natasha
Abstract: Background: Driving is a complex task requiring multiple cognitive domains and the musculoskeletal system. Cognitive dysfunction is associated with driving impairment. Dialysis patients are known to have a high prevalence of cognitive impairment and other comorbidities, and may be at risk of driving impairment. No Australian guidelines address driving safety in dialysis patients. Aims: To estimate the proportion of dialysis patients who were driving and those at risk of driving impairment, and to investigate the agreement between objective and subjective markers of risk. Methods: This single‐centre study involved dialysis patients voluntarily completing two questionnaires relating to risk of driving impairment; the first questionnaire focussed on objective markers, and the second questionnaire focussed on subjective markers. Risk of driving impairment was established using pre‐determined criteria, and the agreement between objective and subjective markers was estimated using Cohen kappa. Results: A total of 44.8% (99/221) of patients participated; 76.8% (76/99) of participants were driving, and 76.3% (58/76) of drivers were at risk of driving impairment. Factors associated with at‐risk driving included post dialysis dizziness, leg weakness or numbness, falling asleep while driving and hypoglycaemia. Sixteen patients reported collisions since commencing dialysis. The questionnaires displayed slight agreement (Cohen kappa = 0.20) between objective and subjective markers. Conclusions: Dialysis patients are at risk of driving impairment based on self‐reported questionnaire responses. Discrepancies between patients' perceptions and objective markers were apparent. Further research into appropriate risk assessments, as well as development of guidelines to aid in determining driving safety in dialysis patients, is needed.